Pendidikan Agama Islam dalam Membangun Etika Sosial (Telaah Pemikiran A. Qodri A. Azizy - Afif Muhammad (IAIN Purwokerto, 2014)
Abstract: This study is aimed at knowing 1) how Islamic Education developssocial ethics according to A. Qodri A. Azizy and 2) how Islamic Education developssocial ethics in according to A. Qodri A. Azizy in the present implementation ofIslamic education. This is a literary study in which data were gained from books andarticles written by A. Qodri A. Azizy, especially those related to Islamic education.Data were analyzed with qualitative method. This research found that there arethree main points that are transferred by Islamic education, i.e. values, knowledge,and skills. In relation to social ethics, Islamic education emphasizes that Islamprincipally teaches social moral values in regards with the relationship among humanbeing. The main points of materials in Islamic education include belief (aqidah),worship (syari’ah), and moral (akhlak). With the materials, Islamic education isoriented to social values.Keywords: Islamic education, social ethics, A. Qodri A. Azizy. Abstrak: Hasil penelitian ini menunjukkan ada tiga hal penting yang akanditransfer melalui pendidikan Agama Islam, yaitu nilai (values), pengetahuan(knowledge), dan keterampilan (skills). Kaitannya dengan etika sosial, terletakpada penekanan terpenting dari ajaran Islam yang pada dasarnya adalah hubungansesama manusia yang sarat dengan nilai-nilai yang berkaitan dengan moralitassosial. Inti materi PAI meliputi; keimanan (akidah), keislaman (syari’ah), dan ikhsan(akhlak). Tiga ajaran inti ini kemudian dijabarkan dalam bentuk rukun Iman, rukunIslam, dan Akhlak; dan beberapa keilmuan: ilmu tauhid, ilmu fiqh dan ilmu akhlak.Berdasarkan materi-materi tersebut, PAI berorientasi pada nilai-nilai sosial kemasyarakatan.Kata Kunci: Pendidikan Agama Islam dan Etika Sosial.